Collective Risk Generalization to Creditrisk+ - Reza Habibi (Journal of Risk Analysis and Crisis Response (JRACR), 2018)
Using the collective risk models of actuarial science, the Creditrisk+ is extended to the case of random number obligors. First, mathematical methods to compute the distribution of total loss are studied. Then, the mathematical results are applied and verified numerically. The insufficiency data in risk management is a big problem. Thus, the case of data scarce is studied using a Bayesian approach. Finally, a concluding remarks section is also given.